Class III Subdivision Malocclusion With Unilateral Posterior Crossbite - Suresh, R (Kathmandu University Medical Journal, 2015)
This article describes the management of class III subdivision malocclusion with unilateral left side posterior crossbite in an adolescent girl, using rapid palatal expansion followed by extraction of four premolars with comprehensive fixed appliance mechanotherapy.Kathmandu University Medical Journal Vol.12(3) 2014; 207-210